140k views
0 votes
If tanθ = m/n, prove that: (m sinθ - n cosθ)/(m sinθ + n cosθ) = (m² - n²)/(m² + n²)​

User Grindking
by
5.4k points

1 Answer

2 votes

Explanation:


\large\underline{\sf{Given \:Question - }}


\sf \: tan\theta = (m)/(n), \: prove \: that \: (msin\theta - ncos\theta)/(msin\theta + ncos\theta) = \frac{ {m}^(2) - {n}^(2) }{ {m}^(2) + {n}^(2) }


\green{\large\underline{\sf{Solution-}}}

Given that


\red{\rm :\longmapsto\:tan\theta = (m)/(n) }

Now, Consider


\rm :\longmapsto\:(msin\theta - ncos\theta)/(msin\theta + ncos\theta)


\rm \:  =  \: (cos\theta\bigg[m(sin\theta)/(cos\theta) - n\bigg])/(cos\theta\bigg[m(sin\theta)/(cos\theta) + n\bigg])


\rm \:  =  \: (mtan\theta - n)/(mtan\theta + n)


\rm \:  =  \: (m * (m)/(n) - n)/(m * (m)/(n) + n)


\rm \:  =  \: \frac{\frac{ {m}^(2) }{n} - n}{\frac{ {m}^(2) }{n} + n}


\rm \:  =  \: \frac{\frac{ {m}^(2) - {n}^(2) }{n}}{\frac{ {m}^(2) + {n}^(2) }{n}}


\rm \:  =  \: \frac{ {m}^(2) - {n}^(2) }{ {m}^(2) + {n}^(2) }

Hence,


\red{\sf \: tan\theta = (m)/(n), \: \rm \implies\: \: (msin\theta - ncos\theta)/(msin\theta + ncos\theta) = \frac{ {m}^(2) - {n}^(2) }{ {m}^(2) + {n}^(2) }}

▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬

Additional Information:-

Relationship between sides and T ratios

sin θ = Opposite Side/Hypotenuse

cos θ = Adjacent Side/Hypotenuse

tan θ = Opposite Side/Adjacent Side

sec θ = Hypotenuse/Adjacent Side

cosec θ = Hypotenuse/Opposite Side

cot θ = Adjacent Side/Opposite Side

Reciprocal Identities

cosec θ = 1/sin θ

sec θ = 1/cos θ

cot θ = 1/tan θ

sin θ = 1/cosec θ

cos θ = 1/sec θ

tan θ = 1/cot θ

Co-function Identities

sin (90°−x) = cos x

cos (90°−x) = sin x

tan (90°−x) = cot x

cot (90°−x) = tan x

sec (90°−x) = cosec x

cosec (90°−x) = sec x

Fundamental Trigonometric Identities

sin²θ + cos²θ = 1

sec²θ - tan²θ = 1

cosec²θ - cot²θ = 1

User Florian Jacta
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.